2020
DOI: 10.1101/2020.05.28.122291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lung cancer models reveal SARS-CoV-2-induced EMT contributes to COVID-19 pathophysiology

Abstract: COVID-19 is an infectious disease caused by SARS-CoV-2, which enters host cells via the cell surface proteins ACE2 and TMPRSS2. Using normal and malignant models and tissues from the aerodigestive and respiratory tracts, we investigated the expression and regulation of ACE2 and TMPRSS2. We find that ACE2 expression is restricted to a select population of highly epithelial cells and is repressed by ZEB1, in concert with ZEB1's established role in promoting epithelial to mesenchymal transition (EMT). Notably, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 101 publications
2
54
1
Order By: Relevance
“…Of note in the context of these data is the fact that signaling through two SARS2 cellular receptors, ACE2/AT2 and CD147/basigin, has been linked to EMT in the context of organ fibrosis [87][88][89] . Finally, while this manuscript was under review, a preprint was posted that described EMT-like transcriptional and metabolic changes in response to SARS2 infection 90 . Collectively, our data indicate that EMT warrants further investigation as a SARS2-specific pathological mechanism.…”
Section: Hypothesis Generation Use Case 3: Association Of An Epithelimentioning
confidence: 99%
“…Of note in the context of these data is the fact that signaling through two SARS2 cellular receptors, ACE2/AT2 and CD147/basigin, has been linked to EMT in the context of organ fibrosis [87][88][89] . Finally, while this manuscript was under review, a preprint was posted that described EMT-like transcriptional and metabolic changes in response to SARS2 infection 90 . Collectively, our data indicate that EMT warrants further investigation as a SARS2-specific pathological mechanism.…”
Section: Hypothesis Generation Use Case 3: Association Of An Epithelimentioning
confidence: 99%
“…On the other hand, ACE2 gene expression positively correlated with infiltration level of immune cells including memory B cell, plasma B cell, activated myeloid dendritic cell, and resting myeloid dendritic cell in COAD patients [59]. SARS-CoV-2 infection was shown to reduce ACE2 level post-infection [58], which would bring poor prognosis for patients with colon cancer due to altered immune cell infiltration level. In a landscape profiling analysis on the expression level of ACE2 in pan-cancers, Dai et al [60] showed that ACE2 was significantly differentially expressed in six types of cancer.…”
Section: Role Of Molecular Aberrations and Genetic Changes Associatedmentioning
confidence: 95%
“…Singh et al [57] showed that the S2 subunit of SARS-CoV-2 strongly interacts with the well-known tumor suppressor proteins, p53 and BRCA-1/2. These proteins regulate various downstream signaling pathways and are frequently mutated in human cancer suggesting the need for further research to understand COVID-19 effect in cancer patients [58].…”
Section: Role Of Molecular Aberrations and Genetic Changes Associatedmentioning
confidence: 99%
See 1 more Smart Citation
“…The Fourier transform infrared spectroscopy (FTIR) is a technique that allows analyzing the molecular structure of a sample through a signal or FTIR spectrum produced by the vibrations of the chemical bonds that make up said sample when impacted by frequencies belonging to infrared radiation [3] . By producing molecular changes [4] [5] , viral infections are potentially identifiable by FTIR spectroscopy, so this technique can be advantageous to perform examinations in a more agile way than RT-PCR (72 hours on average) [6] Through different regions of the FTIR spectrum, it has been possible to detect characteristic changes of different types of cancer, Parkinson's disease, and diabetes, among other diseases [7] [8] [9] , however, related to viral infections, Supti R, et al, and Eyal A, et al [10] [11] , indicate that viral infections mainly affect the protein region, specifically the region attributed to amide I (1700-1600 cm -1 ). Spectral changes are reflected by the growth or decrease in a region of the FTIR spectrum, so transforming the spectrum, Figure 1a, through the use of derivatives, Figure 1b, helps to highlight such changes as in the work of Supti R, et al [10] .…”
mentioning
confidence: 99%